Development of a Herbal Formula of Breadfruit (Artocarpus altilis) Leaf Extract for Fluid Retention Management in Congestive Heart Failure - Kasron Kasron; Susilawati Susilawati; Asep Nurrahman (Indonesian Journal of Global Health Research, 2026)
Congestive heart failure (CHF) is characterized by persistent fluid retention leading to edema and dyspnea, which significantly impair functional capacity and increase hospital readmission rates. Although loop and thiazide diuretics are effective in decongestion, long-term use frequently results in electrolyte imbalance, renal dysfunction, and diuretic resistance. Breadfruit leaf (Artocarpus altilis), containing flavonoids, tannins, and saponins with natural diuretic mechanisms, has been traditionally used to reduce fluid accumulation and edema. This study aimed to evaluate the effectiveness of standardized breadfruit leaf extract in improving fluid retention and dyspnea among CHF patients. This study aimed to evaluate the effectiveness of standardized breadfruit leaf (Artocarpus altilis) extract in reducing fluid retention and improving dyspnea in patients with congestive heart failure (CHF). A quasi-experimental one-group pretest–posttest design was conducted on 15 CHF patients who received standardized breadfruit leaf extract for five consecutive days. Parameters measured included body weight and dyspnea severity using the Borg Modification Scale. Data were analyzed using paired t-tests. A statistically significant reduction in body weight was observed after intervention (61.9 ± 5.2 kg to 61.7 ± 5.2 kg; p = 0.005), indicating decreased fluid retention. Dyspnea scores also showed significant improvement (5.6 ± 0.6 to 4.5 ± 0.8; p = 0.001), reflecting meaningful clinical relief in respiratory symptoms associated with congestion. Standardized breadfruit leaf extract demonstrated beneficial effects in reducing body fluid accumulation and improving dyspnea among CHF patients, supporting its potential as a complementary therapy with minimal adverse effects.